Bob Ahrens interview [part 3, 2008] - EKOS Communications; Elders Council for Parks in British Columbia; Searle, D. Richard (Donald Richard), 1951 (2008)
Interview conducted by Rick (D. Richard) Searle, April 2008. Ahrens interview running time: 00:00-40:08, QuickTime H.264 file. Some background noise 11:57 and 19:50. Video cuts out at 29:50 and resumes at 29:55. Donated to UVic Archives in 2008 by Rick Searle executive producer of EKOS Communications. Continuation of 2008 Ahrens interview. Ahrens continues to discuss BC Parks’ interpretation program, including internal critics, and tells an anecdote about being “too practical” at Rathtrevor Beach and successes at Kokanee Creek Park. He addresses internal dynamics within the organization, but describes an overall esprit de corps, saying there is no one father of the provincial park system; rather, he speaks of numerous groundbreakers, such as Don McMurtry. Ahrens reminisces about beautiful natural places in BC, including seeing Strathcona Park and the Nahatlatch for the first time, plus west coast beaches. He speaks about national park interests in Cape Scott and Pacific Rim, then discusses the Alpine Club of Canada’s involvement in parks such as the Rocky Mountains. Ahrens talks about the “classic” parks like Mount Robson, Assiniboine and Garibaldi and speaks of necessary regulations, like the limitations at Bowron Lake and West Coast Trail. He then addresses consultation with First Nations in parks past, present and future. Ahrens and his interviewers talk about sound recordings and graphic images for Elders Council for Parks of BC projects. Ahrens ends the interview by speaking about his shifting interest from BC Parks; now, he focuses on the larger world and sees problems of parks as a microcosm of bigger in the world. Part of Elders’ Council for Parks in British Columbia oral history interview series, collected for the documentary BC Parks: Celebrating 100 Years of Recreation and Protection available at http://ekoscommunications.com/node/723. Elders Council for Parks in British Columbia; EKOS Communications; Irving K. Barber Learning Centre, British Columbia History Digitization Program (University of ...